KUALITAS SPERMATOZOA MENCIT (MUS MUSCULUS L.) SETELAH PERLAKUAN INFUS KAYU AMARGO (QUASSIA AMARA LINN.) DAN PEMULIHANNYA - ERMAYANTI, NI GUSTI AYU MANIK; SUARNI , NI MADE RAI (Jurnal Biologi Udayana; Vol 14 No 2 (2010): Jurnal Biologi, 2010)
Some studies have indicated that different types of plants can impair male fertility. The research aims to determine the effect of amargo wood intravenous feeding on the quality of mice sperm and its reversibility. The research design used was Random Full Factorial Design. Thirty male mice were divided into two groups of observations, i.e. group I (35 days after infusion) and group II (14 days after administration of infusion discontinued). Furthermore, each group was further subdivided into five sub-dose treatment groups, namely 0 (control), 0 (placebo), 1000, 2000, and 4000 mg/kg. Infusion was administered orally, once daily, for 35 days with a volume of 1 ml. The quality of sperm observed includes motility, viability, and morphology. The data obtained were tested by Anova. The result showed that amargo wood intravenous treatment has significant effect (P<0,05) on sperm quality and there are significant differences between group I and group II. For the observation of group I, the greater the infusion dose given will cause a decrease in sperm quality and for group II infusion decreases the effect and shows an improvement of sperm quality, but not yet recovered to its first condition. It was concluded that amargo wood infusion can reduce the sperm quality of mice and reversible in nature.
Keywords: amargo wood; sperm quality; epididymis; fertility